TRANSLATING IDIOLECTAL FEATURES AND CONCEPTUAL MEANING IN MODERNIST PROSE WITH REFERENCE TO HEMINGWAY (Symposium on Life and Environmental Sciences, 2026)
The article investigates the problem of translating idiolectal features and conceptual meaning in modernist prose, with special attention to Ernest Hemingway’s minimalist style. The study argues that in Hemingway’s works the authorial conceptosphere is activated not by explicit explanation but by short sentences, repetition, silence, pauses, limited evaluation and metaphorical contrasts. These features construct concepts such as courage, fear, endurance, loneliness and death. When such features are simplified or explained in translation, the conceptual layer of the original may be weakened. The paper analyzes several examples from The Old Man and the Sea, A Farewell to Arms and The Snows of Kilimanjaro and Other Stories, comparing the original passages with possible Uzbek translations. The article proposes controlled expansion, rhythmic correspondence, compensation and loyalty to minimalism as productive strategies for translating modernist idiolect. The study concludes that literary translation should preserve not only lexical meaning but also the cognitive-stylistic mechanisms through which the author’s conceptual world is created.
Keywords: literary translation, Hemingway, idiolect, conceptosphere, modernist prose, implicit meaning, translation strategy